Drug-Coated Balloon for the Treatment of Femoropopliteal Tosaka Class III In-stent Restenosis Lesions - Zhang, Bihui; Niu, Guochen; Yan, Ziguang; Zou, Yinghua; Tong, Xiaoqiang; Yang, Min (Frontiers in Surgery, 2021)
Background: To date, there have been few studies examining the efficacy and safety of drug-coated balloon (DCB) angioplasty in the treatment of Tosaka class III in-stent restenosis (ISR) lesions in the clinical setting. Therefore, this study aimed to investigate the clinical efficacy and safety of DCBs in patients with Tosaka class III ISR femoropopliteal lesions. Methods: This single-center study enrolled 28 femoropopliteal ISR Tosaka III patients who were treated by DCB angioplasty from September 2016 to September 2018. The patency, the freedom from target lesion revascularization (TLR) rate, clinical improvement, and safety endpoints were analyzed during a 14-month follow-up period. Results: Out of the 28 patients, 32.1% presented with critical limb ischemia. The mean lesion length was 250.4 ± 93.9 mm. Technical success was achieved in all lesions (100%). Debulking devices were used in 50% of lesions, and bailout stents were performed in 3.6% of patients. Kaplan Meier estimates that the 14-month primary patency was 79.2% (95% CI 60.6–97.8%), whereas the freedom from TLR rate was 91.5% (95% CI 80.1–100%). Clinical symptoms improved by at least 1 Rutherford category in 82.1% of limbs. The ankle-brachial index (ABI) values improved from 0.51 ± 0.30 to 1.05 ± 0.22 at the final follow-up (P < 0.001). The rate of freedom from 30-day major adverse limb events (MALEs) was 100%. The mortality rate was 7.1%. Conclusion: These results suggested that the use of DCBs is safe and effective in treating femoropopliteal Tosaka class III ISR lesions.